Analisis Pergantian Alat Pengencang Baut-U 4 Spindel Menjadi 1 Spindel di Station Rear axle PT.Daimler Commercial Vehicles Manufacturing Indonesia - Natanael Charisma Agape (Jurusan Teknik Mesin, Universitas Halu Oleo, 2022)
Bolt tightening is a process that is widely and important to use or do in the vehicle assembly process.. Power tools with synchronous systems are powerful equipment that is able to help the process of tightening several bolts simultaneously without human energy. This study aims to analyze the 1 spindle bolt fastener to fasten 4 U-bolts on Rear axle in Axor 4028TT type trucks at PT. Daimler Commercial Vehicles Manufacturing Indonesia.The experiment was conducted to test the fastening of the bolt 1 spindle with a replica method of the 4 spindle bolt fastening synchronization system. Sampling used is 6 units with each unit has 4 bolts on the right and left to be compared with the results of U-bolt tightening using the tool 4 spindles.The study used a digital moment key to measure the residual firmness value of the bolt. The data analysis technique is to compare the value of the bolt tightening deviation across two tool systems. The average deviation value on the 1 spindle bolt fastener is 0.31% while on 4 spindles it is 0.13%. The average value of deviations from the digital moment key verification results on 1 spindle is 2.4% while 4 spindles are 3.4%. The results of the comparison showed that the results of fastening bolts 1 spindle provide a deviation of no more than ± 18.6%. Despite having a deviation value greater than 4 spindles, but considering the capacity of units produced in the pandemic period and cost components if tool repairs are made, then the 1 spindle bolt tightening tool is worth considering for use..